CD31‐labeled circulating endothelial cells as predictor in anlotinib‐treated non‐small‐cell lung cancer: Analysis on ALTER‐0303 study - Zhujun Liu (Cancer Medicine, 2018)
Abstract Our previous studies revealed that the level of activated circulating endothelial cells (aCECs) was correlated with the progression‐free survival (PFS) in antiangiogenesis therapy. Anlotinib displayed affirmatory efficacies in several clinical trials of non‐small‐cell lung cancer (NSCLC). To find a marker predicting the efficacy of anlotinib treatment, we investigated the correlations of aCECs with PFS and overall survival (OS) in patients with NSCLC treated with anlotinib and the impact of anlotinib on human umbilical vascular endothelial cells (HUVECs). The blood samples of 78 patients with NSCLC were collected. aCECs were identified by flow cytometry as CD45−/CD146+/CD31+ cells and CD45−/CD146+/CD105+ cells. The mean value of baseline aCECs counts was defined as the cutoff value, according to which patients were divided into high and low baseline groups. Statistical correlation between high baseline CD31‐labeled aCECs counts and number of metastatic lesions (>3) (χ2 = 4.905, P = .027) was analyzed. The 49 patients treated with anlotinib were stratified according to the ratio of minimal aCECs counts at any time points to baseline (aCECs min/baseline) as <1 or ≥1. Interestingly, the patients with aCECs (CD31) min/baseline <1 displayed longer PFS [HR = 0.439, 95%CI (0.211‐0.912), P = .023]. The biological effect of anlotinib on HUVECs was investigated using MTT assays. Western blot analysis was conducted to evaluate the expression levels of CD31 and CD105 under anlotinib treatment and the underlying mechanisms. In vitro experiment data demonstrated that CD31 exhibited more sensitive changes than CD105 under anlotinib treatment through PI3K‐AKT pathway. Thus, our finding provides new insights into the mechanism by which the CD31‐labeled aCECs are a more sensitive marker for predicting the efficiency of anlotinib treatment.